Learning Media in Indonesian Higher Education in Industry 4.0: Case Study - Rizal Rizal; Misnasanti Misnasanti; Syahrial Shaddiq; Ramdhani Ramdhani; Feri Wagiono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
The aims of this research was to fill the theoretical and empirical gaps about the case study with regard to learning media in Indonesia's higher education in industry 4.0 and society 5.0 era. This research used qualitative methods. Data collection techniques used interviews, observations, and documentation. The results of this study revealed tht virtual learning (VL) media ws an effective learning media in Indonesian higher education in industry 4.0 and society 5.0. Therefore, the use of relevant learning models was in line with the times, and the use of more flexible VL media was a strategy to enhance educational quality in the Unitary State of the Republic of Indonesia. Keywords: Learning Media, Education in Industry 4.0, Higher Education